How convenient is it? Delivering online shopping convenience to enhance customer satisfaction and encourage e-WOM - Duarte, Paulo (2018)
The purpose of this article is to identify which dimensions of online convenience affect consumers’ intention of using online shopping and explore a conceptual model to measuring consumer perceptions of online shopping convenience in order to surpass the shortcomings of previous studies that did not examine the consequences of convenience shopping experience. A sample of 250 Portuguese young individuals participate in the empirical study. Confirmatory Factor Analysis (CFA) and a covariance-based Structural Equation Model (CB-SEM) were used to validate the measurement model and to test the relationships in the model. The results reveal that possession, Transaction, and Evaluation are the dimensions with more influence in online shopping convenience. The outcomes of this study extend previous works on online convenience and help to understand which factors drive online satisfaction and enhance behavioral intentions and e-WOM. Contributions to the body of knowledge and the implications for e-commerce retailers are presented. In face of the findings, retailers should be conscious that customer expectations of online convenience have increased as a natural response to the service innovations introduced by website managers and marketers. Therefore, frequent monitoring of consumers’ perceptions and expectations about online convenience is a prerequisite for achieving continuous improvement in rendering highly convenient online service.